The Role of Brain MRI in Mitochondrial Neurogastrointestinal Encephalomyopathy. Issue 5 (October 2013) - Scarpelli, Mauro; Ricciardi, Giuseppe Kenneth; Beltramello, Alberto; Zocca, Isabella; Calabria, Francesca; Russignan, Anna; Zappini, Francesca; Cotelli, Maria Sofia; Padovani, Alessandro; Tomelleri, Giuliano; Filosto, Massimiliano; Tonin, Paola
Leukoencephalopathy is a hallmark of mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) a devastating disorder characterized by ptosis, ophthalmoparesis, gastrointestinal dysfunction and polyneuropathy. To characterize MNGIE-associated leukoencephalopathy and to correlate it with clinical, biochemical and molecular data, four MNGIE patients with heterogeneous clinical phenotypes (enteropathic arthritis, exercise intolerance, CIDP-like phenotype and typical presentation) were studied by magnetic resonance imaging (MRI) and magnetic resonance spectroscopy (MRS). Diffusion weighted imaging (DWI) with apparent diffusion coefficient (ADC) maps were also obtained. In two patients we also investigated the role of brain MRI in monitoring the evolution of leukoencephalopathy by performing follow-up imaging studies at an interval of one and two years. The extension and distribution of leukoencephalopathy were not clearly linked with age, phenotype or disease severity, and did not seem to be related to TYMP mutations, enzyme activity or pyrimidine levels. In the studied patients MRS revealed reduced N-acetyl-aspartate and increased choline signals. Although DWI appeared normal in all patients but one, ADC maps always showed moderate increased diffusivity. Leukoencephalopathy worsened over a two-year period in two patients, regardless of the clinical course, indicating a lack of correlation between clinical phenotype, size and progression of white matter abnormalities during this period. Brain MRI should be considered a very useful tool to diagnose both classical and atypical MNGIE. Serial MRIs in untreated and treated MNGIE patients will help to establish whether the leukoencephalopathy is a reversible condition or not.